Tokoh Wanita Profeminis dan Kontrafeminis dalam Novel Firdaus yang Hilang Karya Mira W - Syahfitri, Meilisa; Abdurahman, Abdurahman; Tamsin, Andria Catri (Universitas Negeri Padang, 2013)
The purposeof this studyweredescribe: (1) self-image and social image profeminis character women, (2) self-image and social image kontrafeminis character women. The data of this study were female character and image of women. Sources of data in this study is novel Paradise Lost MiraW works published by PT Gramedia Pustaka Utama in 2010. Data collected with descriptive methods and techniques detailed description. The study's findings are image profeminis figures in the novel Paradise Lost, among others Wiwiek Sartono, Tina and Lina. The characters in the novel kontrafeminis Paradise Lost, among others Lestari Prihatini, Mother, Intan Inawati, Lila and Bi Umi. Images of women in this novel consists of : (1) women's self-image that reflects the character of adult women who choose and determine attitudes and feelings through reasonableness, (2) the social image of women that reflects the character is good or bad behavior of leaders in the community.